The presence of REE in titanite, garnet and epidote from the Aitik mine tailings - Klapp, Rasmus (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2018)
The aim of this thesis is to investigate the rare earth element (REE) distribution within titanite, garnet and epidote from the Aitik mine tailings, the waste material of a large porphyry-copper deposit mined in northern Sweden. The mine is an open pit operation with a low grade – high tonnage ore that generates roughly 36 Mt of tailings annually. REE are considered critical metals as they are very important for the industry and the society. They are also only extracted in a few locations around the world which implies a substantial risk of supply shortage. It is therefore necessary to increase the exploration and understanding of REE in many types of deposits, including the Aitik deposit. Linking the REE distribution of these minerals with the geological evolution of the Aitik deposit is a second aim of this thesis, in order to further increase the knowledge of the Aitik deposit and the behaviour of REE. A sample taken from the Aitik tailings material was examined by micro-analytical techniques including optical microscope, SEM and finally LA-ICP-MS, generating REE distribution maps of titanite (5 grains), garnet (2 grains) and epidote (2 grains). The results show that REE are present in all titanite grains, with varying abundance within certain areas of the grains. The garnet end epidote showed lower REE signature, mostly bound to fractures within the grains. It is concluded that further investigations on the concentrations of REE should be conducted, and that innovative mineral processing methods will have to be examined before a potential extraction would be considered. Also, based on the REE distribution, the titanite grains are suggested to have undergone trace element migration, consistent with Svecofennian magmatism and metamorphism established for the area.